Safety and efficacy of a plug-based vascular closure device after percutaneous microaxial flow pump in the treatment of complex and high-risk indicated patients - Schröder, Jörg Walter; Mangner, Norman; Woitek, Felix J.; Markus, Kai U.; Lehrke, Michael; Vogt, Felix; Verket, Marlo; Siskos, Alexandros; Biener, Moritz; Meder, Benjamin; Van Mieghem, Nicolas M. (Catheterization and cardiovascular interventions, 2025)
Background Femoral large-bore vascular access is an important and constantly increasing technique in interventional treatment. Temporary circulatory support in complex and high-risk indicated patients (CHIP) presents a challenge in terms of postinterventional access site closure. Aim Monitoring the safety and efficacy of the MANTA system (Teleflex Inc.), a plug-based vascular closure device (PbVCD) in patients receiving a percutaneous microaxial flow pump (mAFP). Methods A multicenter prospective all-comers registry enrolled 73 consecutive patients scheduled for PbVCD after receiving mAFP for CHIP or cardiogenic shock. The primary endpoint was the occurrence of vascular complications at the mAFP access site until discharge according to the Valve Academic Research Consortium-3 (VARC-3) definition. Secondary endpoints included the rate of procedure- or device-related bleedings, device-failures, and the time to hemostasis. Operators rated on the use of the MANTA System and the similarity compared to ANGIOSEAL (Terumo Medical Corp.). Results Hemostasis was achieved in all 73 patients with no need for alternative treatment other than manual compression. The primary endpoint occurred in 7 (9.6%) patients with 1 (1.4%) patient suffering from a major vascular complication and 6 (8.2%) patients developing hematoma with type 2 bleeding (minor vascular complication). There was no vessel closure or thromboembolic event. In-hospital survival was 100%. Conclusions The PbVCD system is a safe, efficient and easy-to-use vascular closure system for large-bore vascular access in patients receiving a mAFP. Advantages and disadvantages of PbVCD and suture-based vascular closure devices (SbVCD) systems should be individually adapted according to the patient's medical history and the anatomy of the vascular constellation.
Veröffentlicht: 10 April 2025
Gesehen am 08.10.2025